A comparison of three different surgery approaches and methods for neurologically intact thoracolumbar fractures: a retrospective study - Chao Zhu; Bin Wang; Jian Yin; Xin Hui Liu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Objectives The purpose of this study was to evaluate and compare the feasibility, safety, and efficacy of conventional open pedicle screw fixation (COPSF), percutaneous pedicle screw fixation (PPSF), and paraspinal posterior open approach pedicle screw fixation (POPSF) for treating neurologically intact thoracolumbar fractures. Methods We retrospectively reviewed 108 patients who were posteriorly stabilized without graft fusion. Among them, 36 patients underwent COPSF, 38 patients underwent PPSF, and 34 patients underwent POPSF. The clinical outcomes, relative operation indexes, and radiological findings were assessed and compared among the 3 groups. Results All of the patients were followed up for a mean time of 20 months. The PPSF group and POPSF group had shorter operation times, lower amounts of intraoperative blood loss, and shorter postoperative hospital stays than the COPSF group (P < 0.05). The radiation times and hospitalization costs were highest in the PPSF group (P < 0.05). Every group exhibited significant improvements in the Cobb angle (CA) and the vertebral body angle (VBA) correction (all P < 0.05). The COPSF group and the POPSF group had better improvements than the PPSF group at 3 days postoperation and the POPSF group had the best improvements in the last follow-up (P < 0.05). Conclusion Both PPSF and POPSF achieved similar effects as COPSF while also resulting in lower incidences of injury. PPSF is more advantageous in the early rehabilitation time period, compared with COPSF, but POPSF is a better option when considering the long-term effects, the costs of treatment, and the radiation times.